El mundo obrero en la prensa masónica: El 1º de mayo de 1890 en el Boletín de Procedimientos del Gran Oriente Ibérico - Enríquez del Árbol, Eduardo (2016)
This communication analyses the opinion of the Spanish Iberian Grand General Council in its Bulletin of Proceedings of the Labor Movement demonstrations of May 1st, 1890 in Madrid, regarding its two main sides: socialism and anarchism.